Cardiovascular disease risk by assigned treatment using the 2013 and 1998 obesity guidelines. Issue 7 (17th May 2016) - Stevens, June; Erber‐Oakkar, Eva; Cui, Zhaohui; Cai, Jianwen; Virani, Salim S.; Di Angelantonio, Emanuele; Wormser, David
Abstract : Objective: The 1998 and the 2013 guidelines on management of overweight and obesity in adults provided algorithms for identification of patients to be treated with weight loss. To date, the cardiovascular disease (CVD) risk in the groups recommended or not recommended for weight loss treatment has not been estimated and compared. Methods: Baseline data for the Atherosclerosis Risk in Communities study were collected between 1987 and 1989 from adults aged 45 to 64 years. Black and White men and women free of CVD were followed over 22.8 years (median), and 2, 907 incident CVD events were recorded. Results: The hazard ratios adjusted for demographic variables in adults not recommended for treatment versus adults recommended for treatment were 0.54 (95% CI: 0.50‐0.59) for the 1998 algorithm and 0.63 (95% CI: 0.58‐0.69) for the 2013 algorithm, respectively. No gender or race differences were detected when the 2013 algorithm was applied, but using the 1998 algorithm, CVD risk between the groups recommended or not recommended for treatment was more pronounced in Black women than in Black men. Conclusions: The 2013 algorithm performed similarly in Black and White men and women but did not improve upon the 1998 algorithm in terms of discriminating risk of CVD.